Framework for leveraging BIM to mitigate disputes in construction projects in Saudi Arabia - Muse, Abdirahman Bashir; Alsuhaibani, Abdullah; Hassanain, Mohammad A.; Alshibani, Adel; Muse, Abdirashid Mohamed (Frontiers in Built Environment, 2026)
Disputes significantly hinder construction projects by affecting timelines, budgets, and stakeholder relations. Building Information Modeling (BIM) offers potential to address these challenges, yet a structured framework linking BIM functionalities to common dispute causes across the project lifecycle remains lacking. This study develops and validates such a framework through engagement with industry practitioners within the Saudi Arabian construction context, where BIM adoption is now mandatory for public-sector projects. Ten leading dispute causes, and their corresponding BIM functionalities were first identified through an extensive literature review. A structured questionnaire was then distributed to practitioners, yielding 87 valid responses, comprising 42 from contractors and 45 from consultants. The Significance Index, descriptive statistics, and Mann–Whitney U test were employed to assess practitioners’ perceptions of BIM’s effectiveness in mitigating specific dispute causes. Results highlight that improved visualization, enhanced collaboration and communication, and improved data management were consistently valued as cross-cutting BIM functionalities across dispute types and project phases. Design coordination and clash detection consistently ranked highest, underscoring their critical role in addressing change orders and design errors. The resulting framework guides owners and practitioners on where to prioritize BIM effort across the project lifecycle to proactively reduce disputes and strengthen project delivery outcomes.